The relationship between performance and biomechanics in middle-distance runners - Trowell, D.; Phillips, E.; Saunders, P.; Bonacci, J. (Sports Biomechanics, 2021)
The present study aimed to identify movement patterns most related to running performance among highly trained middle-distance runners. Eleven male runners performed overground running trials on an indoor running track, and three-dimensional analyses techniques were used to measure running kinematics and kinetics. Performance was measured as season and personal best time over 1500 m. The average velocity during the running trials was 7.2 ± 0.3 m/s. The average season and personal best 1500 m race times were 3:49.7 ± 0:05.8 and 3:46.0 ± 0:08.3 minutes, respectively. Regression analysis revealed that a smaller range of sagittal-plane hip motion during swing, less thorax flexion at toe-off and a smaller ankle plantarflexion angle at contact accounted for 95.7% (p < 0.001) of the variation in season best running performance. Less sagittal-plane hip motion during swing and a smaller ankle plantarflexion angle at contact also explained 79% of the variance in personal best time. Slower middle-distance runners make initial ground contact with a more plantarflexed ankle and greater forward lean of the trunk. We recommend that coaches and runners pay attention to ankle, shank and thorax angles during technical development and training to identify opportunities to optimise middle-distance running mechanics and performance.